Ce-Doped PANI/Fe3O4 Nanocomposites: Electrode Materials for Supercapattery - Pandey, Subash; Neupane, Shova; Gupta, Dipak Kumar; Das, Anju Kumari; Karki, Nabin; Singh, Sanjay; Yadav, Ram Jeewan; Yadav, Amar Prasad (Frontiers in Chemical Engineering, 2021)
In this study, we report on a combined approach to preparing an active electrode material for supercapattery application by making nanocomposites of cerium (Ce) doped polyaniline (PANI) with a different weight percentage of magnetite (Fe3O4). Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analyses supported the interaction of cerium with PANI and the formation of the successful nanocomposite with magnetite nanoparticles. The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analyses showed the uniform and porous morphology of the composites. Cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) were used to test the pseudocapattery behavior of the nanocomposite electrodes in 1.0 M H2SO4. It was found that the pseudocapattery electrode of Ce-doped PANI with 7 wt.% Fe3O4 exhibited a specific capacity of 171 Fg-1 in the potential range of -0.2 V to 1.0 V at the current density of 2.5 Ag-1. Moreover, Ce-doped PANI with 7 wt.% Fe3O4 revealed a power density of 376.6 Wkg-1 along with a maximum energy density of 25.4 Whkg-1 at 2.5 Ag-1. Further, the cyclic stability of Ce-doped PANI with 7 wt.% Fe3O4 was found to be 96.0% after 5,000 cycles. The obtained results suggested that the Ce-doped PANI/Fe3O4 nanocomposites as a promising electrode material candidate for high-performance pseudocapattery applications.